In Vitro Antioxidant and Anti-diabetic Activity of Bark, Flower and Leaf Extracts of Jacaranda mimosifolia D. Don - Maharjan, Sanam; Ranjitkar, Rajeswar; Bhattarai, Kritee; Gurung, Srijana; Bhandari, Devi Prasad (Journal of Plant Resources, 2025)
Jacaranda mimosifolia D. Don. (Bignoniaceae) is an ornamental tree with opposite bipinnate leaves and tender lavender-blue flowers. Knowledge of the phytochemicals present in any plant is important for understanding its biological significance which may lead to the discovery of new alternative therapeutic drugs. This paper aims to investigate the phytochemical profile, antioxidant potential and in vitro antidiabetic activity of the bark, flowers and leaves of J. mimosifolia, extracted using the cold extraction method with various solvents, viz. hexane, acetone, 100% ethanol and 70% hydroethanol. Preliminary phytochemical test of all extracts was performed to determine their chemical constituents. The total phenolic content (TPC) and total flavonoid content (TFC) were calculated using the Folin-Ciocalteu method and aluminium chloride colorimetric assay, respectively. Similarly, the in vitro antioxidant and antidiabetic potentials of all extracts were determined using the diphenylpicrylhydrazyl (DPPH) assay and α -glucosidase inhibition assay, respectively. The qualitative phytochemical test showed the presence of flavonoids, steroids, glycosides, anthocyanins, terpenoids, tannins and carbohydrates (at least in one part of plant) whereas alkaloids and proteins were completely absent in all the plant extracts. In this study, the highest TPC and TFC were shown in acetone bark extract (219.06 ± 19.54 mg GAE g -1) and hexane leaf (449.76 ± 28.89 mg QE g -1) respectively, whereas the highest IC50 for antioxidant activity and anti-diabetic activity were found to be in 100% ethanol bark (56.15 µg mL -1) and hexane flower (92.5% enzyme inhibition), respectively. Due to notable phenolic content, remarkable antioxidant and antidiabetic effects, the phytochemicals present in leaf and flower extracts of J. mimosifolia could be considered for the discovery of a new drug against oxidative stress-induced diseases and diabetes.